Characterization of Protease from Bacillus licheniformis F11.1 as a Bio-Detergent Agent - lmiah, Sitti Nur; Mubarik, Nisa Rachmania; Wahyuntari, Budiasih (UI Scholars Hub, 2018)
Proteases are among the most important enzymes in both food and non-food industries taking up almost 60% of the world enzyme market. This enzyme has been used for many industrial processes, especially in the detergent industry. The purpose of this study was to characterize the protease from Bacillus licheniformis F11.1 as a bio-detergentagent. An enzyme assay of protease activity was used to assess and characterize the protease enzyme from B. licheniformis F11.1. It showed that the highest pH protease activity for alkaline protease occurred at pH 8.0 with a value of 35.00U/mL. Under incubation temperature, the protease had the highest activity at 50 °C with a value of 24.46 U/mL. Protease activity was inhibited by Ca2+,Mn2+, K+, and Na+ions at concentrations of 5 mM. Protease activity can beenhanced by these ions at concentrations of 2 mM. Protease stability can be measured from half-life. Under anincubation temperature of 50 °C, the half-life of the protease at pH 8, 9, and 10 was 108 min, 114 min, and 98 min, respectively. The assay for enzyme stability with an incubation temperature of 60 °C showed half-lives of 92 minutes, 56 minutes, and 61 minutes for pH 6, 9, and 10, respectively. This enzyme was found to be stable with the addition ofdetergent compounds such as sodium dodecyl sulfate (SDS), Triton X-100, ethylenediaminetetraacetic acid (EDTA), and hydrogen peroxide; all under low concentrations. Determination of the molecular weight using SDS-PAGE andzymogram found the molecular weight was 32.90-35.16 kDa. These results showed that the alkaline protease from B.licheniformis F11.1 can be used as a bio-detergent because of its tolerance to various detergent compounds.